Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.36741/jna.v13i2.100
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tekhnik Relaksasi Genggam Jari Terhadap Penurunan Skala Nyeri Pada Klien Post Operasi Apendisitis Di Rsud Kabupaten Sorong Dan Rsud Sele Be Solu Kota Sorong

Abstract: ABSTRAK Pasien post operasi apendisitis sering mengalami nyeri dikarenakan insisi pembedahan. Relaksasi genggam jari adalah teknik non farmakologis untuk mengurangi nyeri. Tujuan penelitian untuk mengetahui pengaruh relaksasi genggam jari terhadap penurunan nyeri dan perbedaan skala nyeri pada pasien post operasi apendisitis di ruang Kakatua dan Melati, RSUD Kabupaten Sorong dan Rumah Sakit Sele Be Solu Kota Sorong. Desain penelitian menggunakan pre-eksperimental dengan pendekatan Non-equivalent Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Finger grip relaxation technique also effective in reducing pain in postappendectomy patients by change the perception of pain. The results of this study are the same as 3 previous studies [2][3][4]. Effectiveness intervention of finger grip relaxation technique is easier to implemented by using a Numeric Rating Scale (NRS).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Finger grip relaxation technique also effective in reducing pain in postappendectomy patients by change the perception of pain. The results of this study are the same as 3 previous studies [2][3][4]. Effectiveness intervention of finger grip relaxation technique is easier to implemented by using a Numeric Rating Scale (NRS).…”
Section: Discussionsupporting
confidence: 77%
“…A total of 3 journals that discuss finger grip relaxation techniques can reduced pain post-appendectomy. Study by Norma, et al, about finger grip relaxation techniques on the reduction pain of post-appendectomy reported that the mean pain scale of the patients was 30,6 mild, 27,8 moderate, and 25,0 severe [2]. The mean of pain scale before given the finger grip relaxation technique was 58,3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations